2017
DOI: 10.18240/ijo.2017.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for photic phenomena after refractive, rotationally asymmetric, multifocal intraocular lens implantation

Abstract: A large pupil center shift and misalignment between the visual and pupillary axis (angle kappa) may play a role in the occurrence of photic phenomena after implantation of rotationally asymmetric MIOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…However, there is a scarcity of studies focusing on factors for the prediction of halo size. 14–16 Therefore, we also analyzed age, postoperative refraction, and pre- and postoperative pupil size as potential predictors of halo size in multifocal IOLs. Moreover, the level of patient discomfort due to the halo was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a scarcity of studies focusing on factors for the prediction of halo size. 14–16 Therefore, we also analyzed age, postoperative refraction, and pre- and postoperative pupil size as potential predictors of halo size in multifocal IOLs. Moreover, the level of patient discomfort due to the halo was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…12 Tchah et al suggested that visual acuity may not always be a good measure of subjective symptoms or patient satisfaction following implantation of multifocal IOL, since it was noticed that although all dissatisfied subjects had subjective visual complaints, their corrected distance visual acuity was 20/20 or better. 5 Welch et al illustrated that the general level of patient satisfaction regarding cataract removal and IOL placement, while high, is still more affected by glare than by any other studied parameter, including UDVA, BCVA, posterior capsular opacification, and anterior capsular overlap of the IOL optic. 13 Concerning the Acrysof IQ ® PanOptix ® , a study in 116 eyes of 58 patients evaluated visual outcomes with a visual satisfaction questionnaire (Catquest 9-SF with 5 added questions), which included photic phenomena, 9 and 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative pupillometry can measure: (i) pupil diameter under photopic (small pupil) and mesopic (wide pupil) lighting conditions, (ii) distance between the pupil center and the visual axis (angle kappa), between the corneal center and the visual axis (angle alpha), and/or between the pupil center and the corneal center, and (iii) distance (spatial shift) from the photopic to the mesopic pupil center (pupil center shift -PCS) [31][32][33]. Regarding PCS, two types of PCS can be evaluated: (i) measured PCS, which results from the values measured under photopic and mesopic lighting conditions, and (ii) interpolated PCS, which depicts the predicted spatial shift between a photopic pupil of 2 mm to a scotopic pupil of 7 mm, and can contribute to the better comparability of the measurements [34].…”
Section: Pupillometrymentioning
confidence: 99%
“…• Visual axis, angle kappa: In pseudophakic presbyopic corrections with implantation of mIOLs, the angle kappa (misalignment between the visual and pupillary axis) [100] should be taken into consideration, especially for hyperopic patients with a large angle kappa [101,102]. It has been found that large angle kappa is correlated with more glare and halos after implantation of mIOLs [86,103].…”
Section: Preoperative Examination and Patient Selectionmentioning
confidence: 99%